Genetic and environmental origins of verbal and performance components of cognitive delay in 2-year-olds. - Eley, T; Bishop, D; Dale, P; Oliver, B; Petrill, SA; Price, T; Purcell, S; Saudino, K; Simonoff, E; Stevenson, J; Plomin, R (American Psychological Association, 1999)
The authors investigated the etiology of several measures of cognitive delay. Verbal (V) and performance (P) abilities were assessed in over 3,000 pairs of 2-year-old twins. Group-differences heritability for general delay (the lowest 5% of the V and P composite) was 35%. However, V and P delays considered independently showed large differences in group heritability (77% for V vs. 40% for P). Specific delays with comorbid cases eliminated showed an even greater difference in group heritability (78% vs. 22%, respectively). The small sample comorbid for both V and P delay also yielded high group heritability for both V (77%) and P (93%) scores. Shared environmental factors also differed in magnitude for V (20%) and P (41%) delays. Because the genetic and environmental origins of V and P delays in infancy differ, they are better considered separately rather than combined into a composite measure of general cognitive delay.